Penitentiary supervision — the Polish model of ensuring the legal and correct performance of imprisonment - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper analyzes the Polish model of ensuring the legal and correct performance of imprisonment and other forms of detention as aresponse to crime. Key issues include indications of: supervision criteria, the range of supervisory powers and the role of the judge in the implementation of imprisonment. The analyzed solutions are very original in their character. They reflect many years of experience of the Polish penitentiary system and constitute amodern part of penitentiary law.
Keywords: kara pozbawienia wolności; nadzór penitencjarny; zapewnienie legalnego i prawidłowego wykonania kary